Social platform use and psychological well-being - Crolic, C; Pal Zubcsek, P; Stephen, AT; Brooks, G (Wiley, 2024)
Social platforms facilitate the daily interactions of billions of people globally. Prior research generally concludes that social platforms negatively affect people’s welfare. This research reopens this debate by using a robust methodology to examine the time series effects of social platform use on users’ subjective well-being, psychological well-being, physical health, and financial security. We report a six-month longitudinal study of 1,029 adults. Participants’ daily time using social platforms on their mobile device was unobtrusively tracked and their well-being was measured every two weeks. The findings suggest a small, positive effect of time spent using social platforms on both subjective well-being and psychological well-being (but no significant effects on physical health or financial security). Further, it is time spent using social platforms that facilitate interactions with intimate/close ties, that is correlated with positive subjective and psychological well-being.